Effects of flame retardant tributyl phosphate on early development of zebrafish - Yao LI; Jingying ZHU; Yao LI; Limei CHEN; Pengfei ZHU; Xinliang DING; Weijie ZHOU (环境与职业医学)
BackgroundTributyl phosphate (TBP) is widely used as an organophosphate flame retardant. However, there are limited studies on the toxicity of TBP to aquatic organisms at low levels of exposure. ObjectiveTo investigate the effects of TBP on early development of zebrafish (Danio rerio). MethodsZebrafish embryos were randomly divided into four groups at 2 h post-fertilisation (2 hpf), namely, the 0.01% dimethyl sulfoxide (DMSO) control group and TBP exposure groups (0.02, 0.2 and 2 μg·L−1). The exposure time was from 2 hpf to 120 hpf and the hatching rate, malformation rate, heart rate and body length of zebrafish embryos at 72 hpf, the frequency of tail curling at 24-29 hpf, the locomotor ability at 96 hpf and the survival rate at 120 hpf were evaluated, respectively. The whole-body triiodothyronine (T3) and tetraiodothyronine (T4) levels of juvenile fish were measured by enzyme immunoassay at the end of the infection, and the expression levels of hypothalamic-pituitary-thyroid axis (HPT) and neurodevelopmental-related genes were detected by quantitative real-time PCR (q-PCR). ResultsThe heart rates of zebrafish embryos were significantly decreased in all TBP-treated groups (P<0.001), the survival rates of the 0.02 and 2 μg·L−1 TBP groups were significantly decreased (P<0.05), and the malformation rate of the 2 μg·L−1 treated group was significantly increased (P<0.05), which was mainly manifested by pericardial oedema. The frequency of tail curling of zebrafish embryos in all groups reached the highest at 25 hpf, which was significantly lower (P<0.001) in all exposure groups than in the control group (P<0.001). In the locomotor behaviour experiments, the swimming speed of zebrafish larvae in the dark cycle was significantly decreased in the 0.02 and 0.2 μg·L−1 TBP groups (P<0.05), and similar results were found for the light cycle in the 0.2 and 2 μg·L−1 TBP groups (P<0.05). Compared with the control group, the T3 level of zebrafish juveniles in the 0.2 μg·L−1 TBP group increased significantly (P<0.05). The q-PCR results showed that the expression levels of HTP axis-related genes [thyroid hormone receptors (trα, \begin{document}$tr\beta $\end{document}), thyroglobulin (tg), and sodium/iodide co-transporter (nis)] were significantly down-regulated in the exposure groups, the expression level of transthyretin (ttr) was significantly up-regulated in the 0.02 μg·L−1 TBP group, and the iodothyronine deiodinase 2 (dio2) expression level was significantly down-regulated in the 0.02 μg·L−1 TBP group (P<0.05); the neurodevelopment-related gene acetylcholinesterase (ache) was significantly down-regulated in the exposure groups, and the expression levels of myelin basic protein (mbp) and Elav like neuron-specific RNA binding protein 3 (elavl3) were significantly down-regulated in the 0.02 μg·L−1 TBP group (P<0.05). ConclusionTBP exposure can lead to early developmental abnormalities in zebrafish, manifested as developmental toxicity, thyroid endocrine disruption and neurotoxicity during hatching and early juvenile stages.